Effects of body size, habitat selection and exposure on hatchling turtle survival. (18th September 2014) - Paterson, J. E.; Steinberg, B. D.; Litzgus, J. D.
Abstract Iteroparous species invest little energy into annual reproduction and tend to experience low and variable survivorship in young life stages. However, juveniles with traits that increase survival will have a fitness advantage over conspecifics, and usually bigger is better for juvenile vertebrates. Understanding behavioural and morphological characteristics that increase fitness is important for our understanding of the evolution of life‐history strategies. We outfitted naturally emerging hatchlings of two species of turtles (Blanding's turtles Emydoidea blandingii and wood turtles Glyptemys insculpta) with radio transmitters to test five hypotheses related to survival from nests to overwintering sites using logistic regression models. In contrast to the widely supported hypothesis that bigger is better for survival of juveniles, we found that smaller hatchlings of both species were more likely to survive from emergence to overwintering. In E. blandingii, hatchlings that emerged later in the year, which reduced exposure time to predators and environmental risks, and spent less time in upland open habitat, were also more likely to survive. Our results demonstrate that bigger is not always better in juvenile ectotherms. Assuming bigger is better without observations of survival can lead to erroneous conclusions related to fitness proxies and the ontogeny of body size in populations. The observed relationship between habitat selection and survival in E. blandingii indicates a direct link between behaviour (habitat selection) and fitness through mortality caused by predators and environmental stressors.